Kinematic changes using weightliftng shoes on barbell back squat - Sato, K.; Fortenbaugh, D.; Hydock, D. S. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to validate a higher degree of foot segment angle by wearing the weightlifting (WL) shoes and to determine the kinematic differences between WL shoes and running shoes during the barbell back squat. College-aged individuals volunteered to participate in this study (N = 25). After warm-up, subjects performed 60% of 1RM barbell back squat. Reflective markers were placed on lower extremity joints and end of the bar to create segments to analyze kinematics of the barbell back squat from a 2-dimensional view. Three separate repeated measure analyses of variance were used at p = 0.05. Results showed that there was a difference between the footwear conditions; foot segment angle of 3.5° (p < 0.05) and trunk lean of 22 mm (p < 0.05) were captured when wearing WL shoes. However, thigh segment peak flexion angle was not statistically different (p = 0.37). Wearing WL shoes seems to be beneficial in reducing the overall trunk lean, because this position is believed to reduce the amount of shear stress in the lower back area. Back squat with WL shoes also increased foot segment angle and possibly contributes to greater muscle excitation in knee extensors. Weightlifting shoes did not help reach thigh segment closer to horizontal as compared with the running shoe condition. It is recommended that WL shoes be used by those who are prone to displaying a forward trunk lean and who aim to increase knee extensor activation.